PERSPEKTIF PERTANGGUNGJAWABAN PIDANA KORPORASI SEBAGAI PELAKU TINDAK PIDANA KORUPSI - Eddy Rifai (Fakultas Hukum Universitas Gadjah Mada, 2014)
This study examines the perspectives of corporate criminal responsibility as perpetrators of corruption. The research method used normative juridical approach and empirical jurisdiction. The results showed that the regulation of corporate criminal responsibility in criminal corruption has been regulated in the legislation of corruption but are rarely applied in practice. The reluctance of the Public Prosecutor filed a corporate offender to court, because the punishment to be imposed on the corporation only in the form of criminal penalties that have less than the deterrent effect of the death penalty or imprisonment and hardships refutation against the corporation as part elements of the law rather than to prove the guilt of a person accused acquitted result. Penelitian mengkaji tentang perspektif pertanggungjawaban pidana korporasi sebagai pelaku tindak pidana korupsi. Metode penelitian menggunakan pendekatan yuridis normatif dan yuridis empiris. Hasil penelitian menunjukkan bahwa pengaturan pidana tentang pertanggungjawaban pidana korporasi dalam tindak pidana korupsi telah diatur dalam peraturan perundang-undangan tindak pidana korupsi tetapi jarang diterapkan dalam praktik. Keengganan Jaksa Penuntut Umum mengajukan pelaku korporasi ke pengadilan, karena pemidanaan yang akan dikenakan kepada korporasi hanya berupa pidana denda yang kurang mempunyai efek penjera daripada pidana mati atau penjara dan kesulitan pembuktian “kesalahan” korporasi sebagai bagian unsur melawan hukum daripada membuktikan kesalahan orang perorang yang berakibat terdakwa dibebaskan.